Sistemática, evolução e biologia reprodutiva de Utricularia com ênfase para Utricularia amethystina Salzm. Ex A.St.-Hil. & Girard (Lentibulariaceae) - Menezes, Cristine Gobbo [UNESP] (2015)
Utricularia L. is a cosmopolitan genus from Lentibulariaceae and the richest genus in species among the carnivorous plants. Its species are highly polymorphic in many traits such as habit, pollen, seed and trap morphology. Many species has a compact genome resulted from the deletion of non-coding regions, and other peculiar molecular features. Utricularia amethystina is described as one of the most polymorphic species in the genus, it has a complex taxonomic history and is found across the American continents. Its polymorphism is reflected on plant height, corolla's size and shape, and floral pigmentation - U. amethystina might show many shades of purple, yellow and white flowers. However, the most remarkable trait is the polymorphism on pigmentation of flowers, because it might undermine the pollinator attraction, and by this way interrupt the gene flow among its morphotypes. With this in mind, we have surveyed the seed traits, looking for characters useful for taxonomic purposes for U. amethystina and related species. The reproductive strategies found on the genus are also described, focusing on U. amethystina and describing its pollinator. We also have investigated the gene flow among the U. amethystina morphotypes based on barcodes regions from cpDNA. Besides this, were evaluated the evolution of genes related with the transitions on pigmentation of flowers of the Lentibulariaceae. We identified useful seed characters for the genus' taxonomy. U. amethystina is a complex with distinct lineages related one each other with high support from molecular survey with cpDNA, from which only two populations from different floral phenotypes (purple and white) were clustered in all analyses. Some lineages also showed evidences for positive selection on matK gene. The pigmentation evolution showed the expected pattern with purple flowers as the ancestral state from which the transitions occurred. We also observed that the transitions are ...